Decreased Microvascular Cerebral Blood Flow Assessed by Diffuse Correlation Spectroscopy after Repetitive Concussions in Mice. Issue 12 (December 2015) - Buckley, Erin M; Miller, Benjamin F; Golinski, Julianne M; Sadeghian, Homa; McAllister, Lauren M; Vangel, Mark; Ayata, Cenk; Meehan, William P; Franceschini, Maria Angela; Whalen, Michael J
Repetitive concussions are associated with long-term cognitive dysfunction that can be attenuated by increasing the time intervals between concussions; however, biomarkers of the safest rest interval between injuries remain undefined. We hypothesize that deranged cerebral blood flow (CBF) is a candidate biomarker for vulnerability to repetitive concussions. Using a mouse model of human concussion, we examined the effect of single and repetitive concussions on cognition and on an index of CBF (CBFi ) measured with diffuse correlation spectroscopy. After a single mild concussion, CBFi was reduced by 35±4% at 4 hours ( P < 0.01 versus baseline) and returned to preinjury levels by 24 hours. After five concussions spaced 1 day apart, CBFi was also reduced from preinjury levels 4 hours after each concussion but had returned to preinjury levels by 72 hours after the final concussion. Interestingly, in this repetitive concussion model, lower CBFi values measured both preinjury and 4 hours after the third concussion were associated with worse performance on the Morris water maze assessed 72 hours after the final concussion. We conclude that low CBFi measured either before or early on in the evolution of injury caused by repetitive concussions could be a useful predictor of cognitive outcome.